La cultura romantica italiana e la nascita della poesia maltese - Friggieri, Oliver (Études sur la Région Méditerranéenne, 2020)
The older literary tradition in Malta, written in Italian, formed an integral part of the literature of Italy. For centuries Maltese writers considered themselves Maltese through their natural adherence to the modes of thinking and writing of the nearby peninsula, with which Malta forged excellent relations also in the political field. Maltese, the ancient but largely unwritten speech habit of the Maltese people, had no notable history of its own, and was commonly ignored in the cultural and institutional fields. It was through the paramount importance of the Italian cultural heritage in the island that Maltese eventually started to be cultivated on a somehow national scale. The fact that the new romantic principles flourished so strongly in Malta soon led to the inevitable, although belated, acknowlegement of the Maltese language as a medium of literary expression. The birth of poetry in Maltese is due to this direct contact between the two countries.